High-performance silver paste added with nano silver oxide and preparation method of high-performance silver paste

By introducing nano silver oxide into the silver paste of TOPCon solar cells, the problem of fewer contact sites of silver silicon is solved, significantly improving the acetic acid resistance and photoelectric conversion efficiency of the cell, and extending the service life.

CN119418984APending Publication Date: 2025-02-11JIANGSU ZHENGNENG ELECTRONICS TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411695041.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

TOPCon solar cells form fewer silver silicon contact sites in the sintering process, resulting in severe degradation of the cell in acetic acid corrosion, thereby reducing the photoelectric conversion efficiency and service life.

Method used

Nanosilver oxide is introduced as an additive in the silver paste of TOPCon batteries. By adjusting the formula and preparation method of the silver paste, the nanosilver oxide is uniformly dispersed in the silver paste, thereby promoting the formation of silver/silicon contact sites during the sintering process.

Benefits of technology

By introducing nano silver oxide, the acetic acid resistance and photoelectric conversion efficiency of TOPCon batteries are significantly improved, the service life of the battery cells is extended, and the contact resistance between metal and semiconductor is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses high-performance silver paste added with nano silver oxide and a preparation method of the high-performance silver paste. The high-performance silver paste comprises the following components: an organic carrier, glass powder, silver powder and an additive, the organic carrier comprises a volatile solvent and non-volatile resin; the non-volatile resin comprises ethyl cellulose, nitrocellulose, acrylic resin, polyamide wax resin and hydrogenated castor oil; the volatile solvent comprises texanol, diethylene glycol monobutyl ether, diethylene glycol monobutyl ether acetate, tributyl citrate, dimethyl oxalate and dimethyl silicone oil; the additive adopts nano silver oxide. The invention relates to the technical field of solar cells. Compared with silver powder, the nano silver oxide is smaller in particle size, large in specific surface area and low in tap density, the viscosity can be improved when the nano silver oxide is added into the paste, the height-width ratio of a printing grid line electrode can be improved, the shading area can be reduced, the current of a battery piece can be improved, and the photoelectric conversion efficiency of the battery piece can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solar cells, and in particular to a high-performance silver paste added with nano silver oxide and a preparation method thereof. Background Art

[0002] In today's energy field, the development and utilization of solar energy as a clean and renewable energy has received extensive attention. Solar cell technology is the key technology for converting solar energy into electrical energy, among which TOPCon (Tunnel Oxide Passivated Contact) cell technology has become one of the research hotspots due to its advantages in photoelectric conversion efficiency.

[0003] TOPCon cell (Tunnel Oxide Passivated Contact Solar Cell) is a solar cell with tunnel oxide passivated contact based on the principle of selective carriers. TOPCon cells are compatible with P-type cell production lines and can retain and utilize the existing equipment and processes of traditional P-type cells to the greatest extent. The conversion efficiency limit of TOPCon cells is as high as 28.7%. The certified conversion efficiency of mainstream TOPCon manufacturers is as high as 26.89%, and the mass production conversion efficiency reaches 26.1%+. In addition, TOPCon cells have the advantages of low attenuation, high bifaciality, and low temperature coefficient, and the power generation gain effect in terminal power stations is obvious. Therefore, TOPCon has become the mainstream product of photovoltaic cells.

[0004] At present, the grid electrodes of solar cells are usually manufactured by screen printing metal paste, and laser-assisted sintering (LECO) is usually used in the sintering process to improve the processing efficiency and photoelectric conversion efficiency of the cells. However, a serious problem with the TOPCon solar cells produced by the LECO process is that there are few silver-silicon contact sites formed, which causes serious acetic acid corrosion of the cell, greatly reducing the photoelectric conversion efficiency of the cell and affecting the service life of the TOPCon solar cell. In order to solve this problem, changes need to be made to the metal silver electrode paste of the TOPCon cell. Silver oxide thermally decomposes into silver oxide at a temperature of about 300°C. The decomposition temperature of nano silver oxide decreases as the particle size decreases. The following is the chemical formula for the decomposition: 2Ag_2 O=4Ag(s)+O_2(g) The present invention adopts nano silver oxide as an additive and introduces it into the TOPCon battery silver paste, thereby improving acetic acid resistance and conversion efficiency. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a high-performance silver paste with added nano silver oxide, comprising the following components, an organic carrier, glass powder, silver powder and additives; The organic carrier includes a volatile solvent and a non-volatile resin; The non-volatile resin includes ethyl cellulose, nitro cellulose, acrylic resin, polyamide wax resin and hydrogenated castor oil; The volatile solvents include alcohol ester dodecanedione, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, tributyl citrate, dimethyl oxalate and dimethyl silicone oil; The additive is nano silver oxide.

[0006] Furthermore, the silver powder is spherical monodisperse silver powder, and the silver powder accounts for 70-93% in the silver paste; The glass powder is a homemade Pb-B-Bi-Si system glass, and the glass accounts for 1-5% in the silver paste; The nano silver oxide accounts for 0.01-10% in the silver paste; The organic carrier accounts for 7.5-13% of the silver paste; Furthermore, the silver powder accounts for 89% of the silver paste, the glass accounts for 2.5% of the silver paste, the nano silver oxide accounts for 0.3% of the silver paste, and the organic carrier accounts for 8.2% of the silver paste.

[0007] Furthermore, the ethyl cellulose, nitrocellulose, acrylic resin, polyamide wax resin and hydrogenated castor oil account for 5% in the organic carrier.

[0008] Furthermore, the alcohol ester dodecahydrate, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, tributyl citrate, dimethyl oxalate and dimethyl silicone oil account for 85% in the organic carrier.

[0009] Furthermore, the organic carrier also includes 3% coupling agent, 3% thickener, 2% defoamer and 2% leveling agent; Among them, the coupling agent is silane coupling agent KH550, the thickener is sodium carboxymethyl cellulose, the defoamer is polydimethylsiloxane defoamer, and the leveling agent is acrylic leveling agent Modaflow 2100; Furthermore, the average particle size of the nano silver oxide is in the range of 0.5 nm to 600 nm, and the maximum particle size is less than 800 nm.

[0010] Furthermore, the average particle size of the silver powder ranges from 0.8 μm to 3 μm, and the maximum particle size is less than 6 μm.

[0011] Furthermore, the average particle size of the glass powder ranges from 0.8 μm to 3 μm, and the maximum particle size is less than 6 μm.

[0012] Furthermore, the nano silver oxide replaces the silver in the silver paste in the same proportion according to molar percentage, and the molar proportion of the replaced silver powder is 0.25%-1%.

[0013] A method for preparing a high-performance silver paste with added nano silver oxide comprises the following steps: 1) According to the formula, glass powder and organic carrier are weighed and pre-mixed, and then manually stirred and transferred into a centrifugal mixer for pre-mixing; 2) Then, the nano silver oxide powder additive is added for pre-mixing, stirring and centrifugation, mainly to make it evenly dispersed in the slurry; Then, a certain amount of silver powder is added, stirred and centrifuged, and the three different powders are ground with a three-roll grinder to be fully and evenly mixed with the organic carrier to obtain the silver paste for the front side of TOPCon crystalline silicon solar cells.

[0014] The present invention discloses a high-performance silver paste with added nano silver oxide and a preparation method thereof, which has the following beneficial effects: 1) Compared with silver powder, nano silver oxide has a smaller particle size, larger specific surface area and lower tap density. Adding it to the slurry helps to increase the viscosity, which in turn helps to increase the aspect ratio of the printed grid electrode, helps to reduce the shading area and increase the current of the battery cell, thereby improving the photoelectric conversion efficiency of the battery cell.

[0015] 2) Nano-silver oxide is thermally decomposed into nano-silver oxide at a temperature of about 300°C. The introduction of nano-silver oxide in the silver paste helps the formation of silver nanocrystals, which can promote the formation of silver / silicon contact sites, reduce the contact resistance between metal and semiconductor, and form a good ohmic contact in the contact area, thereby improving the current collection efficiency, thereby improving the photoelectric conversion efficiency of the TOPCon battery, and improving the acetic acid corrosion phenomenon.

[0016] 3) The formation of silver nanocrystals formed by the introduced nano-silver oxide is beneficial to reduce the damage of large-particle silver grains to the passivation layer, balance the metal contact, so as to reduce the recombination of electron-hole pairs while maintaining good current collection, thereby improving the photoelectric conversion efficiency of the TOPCon cell.

[0017] 4) Nano-silver oxide reacts with possible glass components in the silver paste during the sintering process. A small number of silver oxide particles are wrapped in glass, and the nano-silver oxide is still wrapped after decomposition. The formed nano-silver can transmit electrons in the form of tunneling effect, improve metal composites, and enhance the photoelectric conversion efficiency of TOPCon batteries. DETAILED DESCRIPTION

[0018] The following specific embodiments further describe the present invention in detail. The embodiments of the present invention are provided for the purpose of illustration and description, and are not intended to be exhaustive or to limit the present invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described to better illustrate the principles and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

[0019] Sample BL, raw materials according to the percentage of each weight: Silver powder: 89% spherical silver powder, particle size D50 is 1.2μm.

[0020] The glass powder content is 2.5%, the glass is a Pb-B-Bi-Si system, and the glass particle size D50 is 1.5μm.

[0021] The organic carrier mainly includes volatile solvents and non-volatile resins. Resins: 1% ethyl cellulose, 1% nitrocellulose, 1% acrylic resin, 1% polyamide wax resin, 1% hydrogenated castor oil. Solvents: 15% alcohol ester, 15% diethylene glycol butyl ether, 15% diethylene glycol butyl ether acetate, 10% tributyl citrate, 10% dimethyl oxalate, and 20% dimethyl silicone oil.

[0022] The organic carrier also includes coupling agent 3%, thickener 3%, defoamer 2% and leveling agent 2%; Among them, the coupling agent is silane coupling agent KH550, the thickener is sodium carboxymethyl cellulose, the defoamer is polydimethylsiloxane defoamer, and the leveling agent is acrylic leveling agent Modaflow 2100; The preparation of the slurry includes the following steps: 1) According to the formula, glass powder and organic carrier are weighed and pre-mixed, and then manually stirred and transferred into a centrifugal mixer for pre-mixing; 2) Then pre-mixing, stirring and centrifuging are performed, mainly to make it evenly dispersed in the slurry; 3) Then add a certain amount of silver powder, stir and centrifuge, grind with a three-roll grinder to fully mix the three different powders with the organic carrier to obtain the silver paste for the front side of the TOPCon crystalline silicon solar cell.

[0023] Example 1: The raw materials are in accordance with the percentage of each weight, and the additive nano silver oxide is substituted for the silver powder in accordance with the molar ratio.

[0024] Silver powder: 89% spherical silver powder, the particle size D50 of the silver powder is 1.2μm, the substitution amount of the additive nano silver oxide accounts for 1% of the molar ratio of the silver powder, and the particle size D50 of the silver oxide is 200nm.

[0025] The glass powder content is 2.5%, the glass is a Pb-B-Bi-Si system, and the glass particle size D50 is 1.5μm.

[0026] The organic carrier mainly includes volatile solvents and non-volatile resins. Resins: 1% ethyl cellulose, 1% nitrocellulose, 1% acrylic resin, 1% polyamide wax resin, 1% hydrogenated castor oil. Solvents: 15% alcohol ester, 15% diethylene glycol butyl ether, 15% diethylene glycol butyl ether acetate, 10% tributyl citrate, 10% dimethyl oxalate, and 20% dimethyl silicone oil.

[0027] The organic carrier also includes coupling agent 3%, thickener 3%, defoamer 2% and leveling agent 2%; Among them, the coupling agent adopts silane coupling agent KH550, the thickener adopts sodium carboxymethyl cellulose, the defoamer adopts polydimethylsiloxane defoamer, and the leveling agent adopts acrylic leveling agent Modaflow 2100.

[0028] The preparation of the slurry includes the following steps: 1) According to the formula, glass powder and organic carrier are weighed and pre-mixed, and then manually stirred and transferred into a centrifugal mixer for pre-mixing; 2) Then, the nano silver oxide powder additive is added for pre-mixing, stirring and centrifugation, mainly to make it evenly dispersed in the slurry; 3) Then add a certain amount of silver powder, stir and centrifuge, grind with a three-roll grinder to fully mix the three different powders with the organic carrier to obtain the silver paste for the front side of the TOPCon crystalline silicon solar cell.

[0029] In Example 2, the raw materials are in accordance with the percentage of each weight, and the additive nano silver oxide replaces the silver powder in accordance with the molar ratio.

[0030] Silver powder: 89% spherical silver powder, the particle size D50 of the silver powder is 1.2μm, the substitution amount of the additive nano silver oxide accounts for 0.5% of the molar ratio of the silver powder, and the particle size D50 of the silver oxide is 200nm.

[0031] The glass powder content is 2.5%, the glass is a Pb-B-Bi-Si system, and the glass particle size D50 is 1.5μm.

[0032] The organic carrier mainly includes volatile solvents and non-volatile resins. Resins: 1% ethyl cellulose, 1% nitrocellulose, 1% acrylic resin, 1% polyamide wax resin, 1% hydrogenated castor oil. Solvents: 15% alcohol ester, 15% diethylene glycol butyl ether, 15% diethylene glycol butyl ether acetate, 10% tributyl citrate, 10% dimethyl oxalate, and 20% dimethyl silicone oil.

[0033] The organic carrier also includes coupling agent 3%, thickener 3%, defoamer 2% and leveling agent 2%; Among them, the coupling agent adopts silane coupling agent KH550, the thickener adopts sodium carboxymethyl cellulose, the defoamer adopts polydimethylsiloxane defoamer, and the leveling agent adopts acrylic leveling agent Modaflow 2100.

[0034] The preparation of the slurry includes the following steps: 1) According to the formula, glass powder and organic carrier are weighed and pre-mixed, and then manually stirred and transferred into a centrifugal mixer for pre-mixing; 2) Then, the nano silver oxide powder additive is added for pre-mixing, stirring and centrifugation, mainly to make it evenly dispersed in the slurry; 3) Then add a certain amount of silver powder, stir and centrifuge, grind with a three-roll grinder to fully mix the three different powders with the organic carrier to obtain the silver paste for the front side of the TOPCon crystalline silicon solar cell.

[0035] Example 3: The raw materials are in accordance with the percentage of each weight, and the additive nano silver oxide replaces the silver powder in accordance with the molar ratio.

[0036] Silver powder: 89% spherical silver powder, the particle size D50 of the silver powder is 1.2μm, the substitution amount of the additive nano silver oxide accounts for 0.25% of the molar ratio of the silver powder, and the particle size D50 of the silver oxide is 200nm.

[0037] The glass powder content is 2.5%, the glass is a Pb-B-Bi-Si system, and the glass particle size D50 is 1.5μm.

[0038] The organic carrier mainly includes volatile solvents and non-volatile resins. Resins: 1% ethyl cellulose, 1% nitrocellulose, 1% acrylic resin, 1% polyamide wax resin, 1% hydrogenated castor oil. Solvents: 15% alcohol ester, 15% diethylene glycol butyl ether, 15% diethylene glycol butyl ether acetate, 10% tributyl citrate, 10% dimethyl oxalate, and 20% dimethyl silicone oil.

[0039] The organic carrier also includes coupling agent 3%, thickener 3%, defoamer 2% and leveling agent 2%; Among them, the coupling agent adopts silane coupling agent KH550, the thickener adopts sodium carboxymethyl cellulose, the defoamer adopts polydimethylsiloxane defoamer, and the leveling agent adopts acrylic leveling agent Modaflow 2100.

[0040] The preparation of the slurry includes the following steps: 1) According to the formula, glass powder and organic carrier are weighed and pre-mixed, and then manually stirred and transferred into a centrifugal mixer for pre-mixing; 2) Then, the nano silver oxide powder additive is added for pre-mixing, stirring and centrifugation, mainly to make it evenly dispersed in the slurry; 3) Then add a certain amount of silver powder, stir and centrifuge, grind with a three-roll grinder to fully mix the three different powders with the organic carrier to obtain the silver paste for the front side of the TOPCon crystalline silicon solar cell.

[0041] The TOPCon silver paste with added nano silver oxide prepared in the above Examples 1-3 was screen printed, and sintered in a belt sintering furnace and laser assisted sintering (LECO) were performed to obtain TOPCon cells. The photoelectric conversion efficiency of the cells was tested using a HalmI-V efficiency tester, and the viscosity of the slurry was tested using a Brookfield viscometer at a rotation speed of 50 r / min.

[0042] Table 1. Performance test results of TOPCon silver pastes of Examples 1-3 and those without adding nano silver oxide

[0043] The slurry without adding nano silver oxide is the standard sample BL. By comparing with BL, it can be seen that: 1) the addition of nano silver oxide has a significant improvement on the current; 2) with the increase of the added content of nano silver oxide, the effect on the opening voltage first increases and then decreases; 3) with the increase of the added content of nano silver oxide, the filling factor FF decreases; 4) the optimal addition content of nano silver oxide is 0.25%; 5) the viscosity of the slurry increases significantly with the addition of nano silver oxide, and the slurry viscosity corresponds to the change of the current.

[0044] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.

Claims

1. A high-performance silver paste with added nano silver oxide, characterized in that: The invention comprises the following components: an organic carrier, glass powder, silver powder and additives; The organic carrier includes a volatile solvent and a non-volatile resin; The non-volatile resin includes ethyl cellulose, nitro cellulose, acrylic resin, polyamide wax resin and hydrogenated castor oil; The volatile solvents include alcohol ester dodecanedione, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, tributyl citrate, dimethyl oxalate and dimethyl silicone oil; The additive is nano silver oxide.

2. The high-performance silver paste with added nano silver oxide according to claim 1, characterized in that: The silver powder is spherical monodispersed silver powder, and the silver powder accounts for 70-93% in the silver paste; The glass powder is a homemade Pb-B-Bi-Si system glass, and the glass accounts for 1-5% in the silver paste; The nano silver oxide accounts for 0.01-10% in the silver paste; The organic carrier accounts for 7.5-13% in the silver paste.

3. The high-performance silver paste with added nano silver oxide according to claim 1, characterized in that: The silver powder accounts for 89% of the silver paste, the glass accounts for 2.5% of the silver paste, the nano silver oxide accounts for 0.3% of the silver paste, and the organic carrier accounts for 8.2% of the silver paste.

4. The high-performance silver paste with added nano silver oxide according to claim 1, characterized in that: The ethyl cellulose, nitrocellulose, acrylic resin, polyamide wax resin and hydrogenated castor oil account for 5-10% in the organic carrier.

5. The high-performance silver paste with added nano silver oxide according to claim 1, characterized in that: The alcohol ester dodecahydrate, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, tributyl citrate, dimethyl oxalate and dimethyl silicone oil account for 80-90% in the organic carrier.

6. The high-performance silver paste with added nano silver oxide according to claim 1, characterized in that: The average particle size of the nano silver oxide is in the range of 0.5nm-600nm, and the maximum particle size is less than 800nm.

7. The high-performance silver paste with added nano silver oxide according to claim 1, characterized in that: The average particle size of the silver powder ranges from 0.8 μm to 3 μm, and the maximum particle size is less than 6 μm.

8. The high-performance silver paste with added nano silver oxide according to claim 1, characterized in that: The average particle size of the glass powder ranges from 0.8 μm to 3 μm, and the maximum particle size is less than 6 μm.

9. The high-performance silver paste with added nano silver oxide according to claim 1, characterized in that: The nano silver oxide replaces the silver in the silver paste in the same proportion according to molar percentage, and the molar proportion of the replaced silver powder is 0.25%-1%.

10. A method for preparing a high-performance silver paste with added nano silver oxide as claimed in any one of claims 1 to 9, characterized in that: The following steps are included: 1) According to the formula, glass powder and organic carrier are weighed and pre-mixed, and then manually stirred and transferred into a centrifugal mixer for pre-mixing; 2) Then, add the nano silver oxide powder additive, pre-mix, stir and centrifuge to make it evenly dispersed in the slurry; 3) Then add a certain amount of silver powder, stir and centrifuge, grind with a three-roll grinder to fully mix the three different powders with the organic carrier to obtain the silver paste for the front side of the TOPCon crystalline silicon solar cell.

Citation Information

Cited By

  • Weldable low-temperature sintered silver paste

    CN120809326A

  • A solderable low temperature sintering silver paste

    CN120809326B